Class IV Composite Restoration of Permanent Maxillary Central Incisor (Case Report) - Muna, Najhatul; Cahyani, C (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Dental fracture is a condition of fracture or partial loss of intact tooth structure caused by trauma or impact, usually occurring in the maxillary incisors. This restorative technique is a minimally invasive treatment for grade IV composite resin restorations that show a good color result. Composite resin can make restorations look worse over time, due to its color instability. The purpose of this article is to know how to make restorations on anterior teeth using composite resin materials. Case report: A 20 years old male visited RSGM Soelastri complaining of a fracture of his tooth, a diagnosis of ellis class II fracture and a treatment plan with a class IV composite resin restoration. Treatment was completed over several visits due to the use of additional mock-up. Control in a month showed that the color was aesthetically acceptable, no discoloration occurred, and the tooth did not fracture. Conclusion: The clinical effectiveness and the associated low failure rates with the composite resin freehand resurfacing technique with mock-ups makes it a great option for restoration of large class IV fractures.